2004
DOI: 10.1158/0008-5472.can-04-1918
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Apoptosis Proteins: Translating Basic Knowledge into Clinical Practice

Abstract: The inhibitor of apoptosis proteins (IAPs) are a family of antiapoptotic proteins that bind and inhibit caspases 3, 7, and/or 9, but not caspase 8. Growing evidence also indicates that IAPs also modulate cell division, cell cycle progression, and signal transduction pathways. As our basic understanding of IAPs has increased, the knowledge is being translated into clinically useful applications in the diagnosis and treatment of malignancy. For example, IAPs such as survivin are being investigated as diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
327
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(339 citation statements)
references
References 85 publications
3
327
0
9
Order By: Relevance
“…We further observed a synergistic inhibition in the phosphorylation of proapoptotic Bad protein at Ser 112 and Ser 136 ( Figure 2d). The inhibitor of apoptosis proteins (IAPs) are a family of antiapoptotic proteins that block cell death, in part, by inhibiting the downstream caspase activation pathways and thus play a critical role in determining cell fate (Liston et al, 2003;Schimmer, 2004). As shown in Figure 3a, we observed a synergistic inhibition of IAP proteins XIAP, cIAP1, Survivin and Smac/Diablo.…”
Section: Egcg Sensitizes Lncap Cells To Trail-mediated Cell Growth Inmentioning
confidence: 73%
“…We further observed a synergistic inhibition in the phosphorylation of proapoptotic Bad protein at Ser 112 and Ser 136 ( Figure 2d). The inhibitor of apoptosis proteins (IAPs) are a family of antiapoptotic proteins that block cell death, in part, by inhibiting the downstream caspase activation pathways and thus play a critical role in determining cell fate (Liston et al, 2003;Schimmer, 2004). As shown in Figure 3a, we observed a synergistic inhibition of IAP proteins XIAP, cIAP1, Survivin and Smac/Diablo.…”
Section: Egcg Sensitizes Lncap Cells To Trail-mediated Cell Growth Inmentioning
confidence: 73%
“…7 It belongs to a family of proteins known as inhibitors of apoptosis (IAPs), which is a family of antiapoptotic proteins that inhibit initiator (caspase-9) and effector (caspase-3 and -7) caspases and thereby prevent apoptosis. 8,9 To date, eight human IAP family members have been identified, and survivin is structurally unique among human IAPs, containing a single baculovirus IAP repeat (BIR) domain and lacking the really interesting new gene (RING) and caspase recruitment domain (CARD) domains. 8,10,11 Survivin is abundantly expressed in embryonic tissues and most tumors; however, it is almost absent in normal differentiated cells.…”
mentioning
confidence: 99%
“…We have previously shown that COX-2 expression is related to a poor prognostic phenotype of DCIS (Boland et al, 2004), but there are no published data on whether COX-2 expression affects recurrence of DCIS. Survivin is a member of the inhibitors of apoptosis protein (IAP) family, which includes proteins such as X-IAP, H-IAP and survivin (Ambrosini et al, 1997;Schimmer, 2004), that have effects on both cell cycle regulation and apoptosis. The antiapoptotic properties of the IAP's lie in their ability to block the activation of caspases (mainly 3, 7 and 9) in the cell cytoplasm, which are key regulators of classical apoptosis (Schimmer, 2004).…”
mentioning
confidence: 99%
“…Survivin is a member of the inhibitors of apoptosis protein (IAP) family, which includes proteins such as X-IAP, H-IAP and survivin (Ambrosini et al, 1997;Schimmer, 2004), that have effects on both cell cycle regulation and apoptosis. The antiapoptotic properties of the IAP's lie in their ability to block the activation of caspases (mainly 3, 7 and 9) in the cell cytoplasm, which are key regulators of classical apoptosis (Schimmer, 2004). In addition to their antiapoptotic effects, IAP's have been shown to regulate cell cycle progression and cell signalling (Schimmer, 2004).…”
mentioning
confidence: 99%